Synthesis, Characterization and Application of Calcium Ion-Imprinted Polymeric Solid-Phase Extraction and Pre-Concentration in Aqueous Solutions by Packed-Bed Columns - Hassoon, Ghaidaa Sabry; Al-Bayati, Yehya Kamal (Iraqi Journal of Science, 2023)
In this work, calcium ions were determined by the addition to the allyl chloride monomer resulting from bulk polymerization formation. To acquire the highest adsorption capacity, molar ratios of the template, monomer, and cross-linking agent, as well as solvents and multiple monomers were investigated. Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were used to analyze the calcium ion polymer. The elution of calcium had a small effect on the surfaces of the three-dimensional network structure. Calcium (II) ions were successfully eluted using a mixture of methanol and acetic acid. The calcium adsorption capacities were 3.8145 and 9.01773 mol/g (Qmax), respectively. A Langmuir isotherm model follows calcium adsorption. Solid-phase extraction (SPE) syringes packed with ionic imprinted polymers (IIPs) were used to selectively separate and preconcentration the calcium (II) ion from aqueous solutions to determine the calcium ion by flame atomic absorption spectroscopy (FAAS).